PELATIHAN DAN PENDAMPINGAN TENTANG PERLAKUAN AKUNTANSI DAN KEUANGAN BAGI MANAJEMEN DAN STAF LPD DESA ADAT LUKLUK - Surya, I.B.K.; Mustanda, I.K.; Abundanti, N.; Sriathi, A.A.A.; Mujiati, N.W.; Utama, W.M.; Dewi, A.A.S.K. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
In restructuring the financial statements are better then the accounting and finance is very important to note. Community service activities is important because during this time the management and staff LPD Lukluk Village People because they lack knowledge of employees on this topic. The purpose of this public service activities is to provide training and guidance on the accounting and finance for the management and staff of the Village People Lukluk LPD. The methods used in problem solving is lecturing and mentoring. Lecture method is used to convey the knowledge of the accounting and finance and its applications in financial services, especially LPD. Mentoring is also used to assist participants in applying the theory gained in practice in the LPD. Trainees are officers, employees, and the Board of Supervisors LPD Village People Lukluk The 13 people who gathered in a room and then given training. Furthermore, once a week to do mentoring to ensure an understanding of the accounting and financial treatment applied in LPD Desa Adat Lukluk. The results showed that the participants training serious training, as demonstrated by their active in the discussion of the problems faced. Assessment of participants of the training is very good. It is suggested that assistance continues to be given to improving the competence of employees in the financial statements.